Molecular organization of tricellular tight junctions - Furuse, Mikio (Landes Bioscience, 2014)
When the apicolateral border of epithelial cells is compared with a polygon, its sides correspond to the apical junctional complex, where cell adhesion molecules assemble from the plasma membranes of two adjacent cells. On the other hand, its vertices correspond to tricellular contacts, where the corners of three cells meet. Vertebrate tricellular contacts have specialized structures of tight junctions, termed tricellular tight junctions (tTJs). tTJs were identified by electron microscopic observations more than 40 years ago, but have been largely forgotten in epithelial cell biology since then. The identification of tricellulin and angulin family proteins as tTJ-associated membrane proteins has enabled us to study tTJs in terms of not only the paracellular barrier function but also unknown characteristics of epithelial cell corners via molecular biological approaches.